Stability control of in-wheel motor drive vehicle with motor fault. (October 2019) - Wang, Hongbo; Cui, Wei; Lin, Shu; Tan, Dongkui; Chen, Wuwei
In-wheel motor drive vehicles have many advantages such as more efficient, energy-saving, large space, and flexible control. But the increase of four-wheel actuators and sensors makes the probability of wheel motor fault increase and brings risk to the safety and reliability of the system. For in-wheel motor drive vehicles, the motor torque output fault happens frequently, which seriously affects the stability and safety of the vehicle. The stability control under the single-motor fault condition is considered in this paper, and the vehicle model with a single-motor fault and the fault diagnosis observer are established. Then, combined with the fault observation, a stability control method is formulated based on the different states of the controlled object of the vehicle. At the stage of low speed and small steering, a torque compensation controller including steady state/feedforward/feedback control is designed for the fault motor based on the triple-step method to ensure the vehicle staying in a stable driving state. At the stage of high-speed, large-steering, or large-torque output, the vehicle stability control based on torque distribution is carried out for the sound wheel, which is composed of a torque tracking controller and a torque optimal distribution controller. The former can make the vehicle get rid of the fault state quickly, and the latter can effectively keep the stability of the vehicle and make the vehicle maintain a certain driving response ability. Finally, the control method proposed in this paper is simulated and tested on the CarSim/Simulink joint simulation platform and the CarSim/LabVIEW hardware-in-loop experiment bench. The results show that after the single-motor fault occurs, the stability control system can effectively suppress the instability of the vehicle caused by the single-motor fault and ensure the stability and safety of the vehicle.